2014
DOI: 10.1039/c3ib40221e
|View full text |Cite
|
Sign up to set email alerts
|

Chemically induced synaptic activity between mixed primary hippocampal co-cultures in a microfluidic system

Abstract: Primary neuronal cultures are an invaluable in vitro tool for examining the fundamental physiological changes that occur in diseases of the central nervous system. In this work, we have used a microfluidic device to grow twin cultures of primary hippocampal neuronal/glia cells which are synaptically connected but environmentally isolated. Immunocytochemical staining, for β-III-Tubulin and synaptophysin, indicated that the two neuronal populations were physically connected and that synapses were present. By dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 26 publications
(54 reference statements)
3
71
0
Order By: Relevance
“…Neurons and glial cells in each chamber grow within the microchannels where they physically interact and form synapses. The function of neuron–glia synapse was confirmed by calcium imaging . Yang et al developed a co‐culture CMS combined with electrodes to study activity‐dependent myelination.…”
Section: Modeling Neurodegenerative Diseases On a Chipmentioning
confidence: 99%
“…Neurons and glial cells in each chamber grow within the microchannels where they physically interact and form synapses. The function of neuron–glia synapse was confirmed by calcium imaging . Yang et al developed a co‐culture CMS combined with electrodes to study activity‐dependent myelination.…”
Section: Modeling Neurodegenerative Diseases On a Chipmentioning
confidence: 99%
“…Typically, to facilitate neuronal culture, microfluidic devices are fabricated using gas-permeable silicone elastomer polydimethylsiloxane (PDMS). The most common device layout used to create synaptically connected but environmentally isolated neuronal populations ( 18 , 19 ) comprises two microfluidic culture compartments where neuronal cells grow processes and subsequently become connected by an array of microchannels through which axonal growth is guided; whether axons or dendrites can reach the opposite culture compartment depends on the length and shape of the microchannels ( 17 , 20 , 21 ). This structure enables axons from one culture compartment to form synaptic connections with dendrites from the other compartment.…”
mentioning
confidence: 99%
“…The authors isolated distal axons from cell bodies in a microfluidic device and concluded that the most susceptible part of the neuron to excitotoxicity is the distal axon [65]. More recently, Roberston et al [66] developed a high-throughput platform to monitor neuronal synaptic communication for drug screening purposes. The authors have combined a microfluidic system with a calcium-imaging array to study primary hippocampal cultured networks.…”
Section: Microfluidic-based Neuronal Circuitsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) images of the 3 μm gaps and apical and basolateral fluidic chamber. Reproduced, with permission, from[66].Version: Postprint (identical content as published paper) This is a self-archived document from i3S -Instituto de Investigação e Inovação em Saúde in the University of Porto Open Repository For Open Access to more of our publications, please visit http://repositorio-aberto.up.pt/ A01/00…”
mentioning
confidence: 99%